Peningkatan Keterampilan Berbahasa Arab Peserta Didik Paket B PKBM Khalifah Cendekia Melalui Video di Krian Sidoarjo - Fatichatus Sa'diyah (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
. Low interest in learning and difficulties in speaking Arabic are experienced by many students. In general, this difficulty occurs due to several factors, both internal and external factors, one of which is the lack of use of appropriate and varied learning media. Thus, the researcher provides a solution to this problem by developing learning media in the form of Arabic learning videos in the form of video visualization to increase students' interest and motivation in learning. The purpose of this research is to find out students' needs for video learning media, as well as the benefits of learning with video visualization. The research design is a Research and Development (R&D) design. The data were obtained from interviews, observations, documentation, and questionnaires in the form of student needs questionnaires for learning media.